Development, implementation and participant evaluation of combining text messaging and peer group support in a weight management programme for African-American women. (August 2020) - Lee, Sohye; Lindquist, Ruth; Schorr, Erica; Chi, Chih-Lin; Treat-Jacobson, Diane J
Background: Development of highly accessible interventions that are effective in reducing body weight, preventing weight gain, and maintaining weight loss is urgently needed to solve the current obesity epidemic, especially among African-American women. Aims: The purpose of this paper is to describe the development, implementation, and participant evaluation processes of a combined text messaging and peer support group programme to enhance weight management skills among African-American women. Methods: The programme's conceptual framework and operational model were developed to enhance the research design and protocol to support the study rationale and to lay a solid theoretical base for programme implementation. The programme curriculum and schedule were established and embedded into the programme protocol. Results: The 16-week text messaging and peer support group intervention was implemented from September 2014 to March 2015. In total, 2089 messages were sent using an online text messaging application. Eight support group sessions were held in the participant's community centre or community church bi-weekly for approximately one hour. Conclusions: This paper provides a blueprint of the methodological aspects and insights from participants' evaluation of a combined weight management intervention that can be used or adapted by public health nurses and other community health professionals in their work to develop weight management skills among African-American women.